Multi‐layered silk film coculture system for human corneal epithelial and stromal stem cells. (28th September 2017) - Gosselin, Emily A.; Torregrosa, Tess; Ghezzi, Chiara E.; Mendelsohn, Alexandra C.; Gomes, Rachel; Funderburgh, James L.; Kaplan, David L.
Abstract: With insufficient options to meet the clinical demand for cornea transplants, one emerging area of emphasis is on cornea tissue engineering. In the present study, the goal was to combine the corneal stroma and epithelium into one coculture system, to monitor both human corneal stromal stem cell (hCSSC) and human corneal epithelial cell (hCE) growth and differentiation into keratocytes and differentiated epithelium in these three‐dimensional tissue systems in vitro . Coculture conditions were first optimized, including the medium, air–liquid interface culture, and surface topography and chemistry of biomaterial scaffold films based on silk protein. The silk was used as scaffolding for both stromal and epithelial tissue layers because it is cell compatible, can be surface patterned, and is optically clear. Next, the effects of proliferating and differentiating hCEs and hCSSCs were studied in this in vitro system, including the effects on cell proliferation, matrix formation by immunochemistry, and gene expression by quantitative reverse transcription–polymerase chain reaction. The incorporation of both cell types into the coculture system demonstrated more complete differentiation and growth for both cell types compared to the corneal stromal cells and corneal epithelial cells alone. Silk films for corneal epithelial culture were optimized to combine a 4.0‐μm‐scale surface pattern with bulk‐loaded collagen type IV. Differentiation of each cell type was in evidence based on increased expression of corneal stroma and epithelial proteins and transcript levels after 6 weeks in coculture on the optimized silk scaffolds.